SPECIES: An R Package for Species Richness Estimation - Ji-Ping Wang (Journal of Statistical Software, 2011)
We introduce an R package SPECIES for species richness or diversity estimation. This package provides simple R functions to compute point and confidence interval estimates of species number from a few nonparametric and semi-parametric methods. For the methods based on nonparametric maximum likelihood estimation, the R functions are wrappers for Fortran codes for better efficiency. All functions in this package are illustrated using real data sets.